My friend Julia : a Sesame Street book about autism - Cook, Jennifer, 1975- (Lerner Publications, 2024)
"We are all amazing because we are all different. Abby, Elmo, and the Sesame Street friends introduce young readers to Julia. Full-color photos and accessible text make this book an age-appropriate introduction to autism"--